Analisis Sisa Lebih Perhitungan Anggaran (SiLPA) Pada Anggaran Pendapatan Belanja Daerah Kabupaten Sikka - Maria Nona Trisna; Henrikus Herdi; Wihelmina M; Yulia Jaeng (Jurnal Riset Akuntansi, 2023)
The implementation of regional autonomy as outlined in Law Number 33 of 2004 provides for the existence of financial considerations between the central government and regional governments. The research was conducted at the Sikka Regency Regional Financial and Asset Management Agency (BPKAD), a new institution formed by Sikka Regency Regional Regulation Number 49 of 2016. The object of the research is the area of ​​regional financial and asset management which is obliged to have the main task of assisting regional heads in government administration. , prepare annual activity reports of regional work units. This research aims to determine the growth of SiLPA in the 2016-2020 Sikka Regency APBD and also to determine the factors in the occurrence of SiLPA in the 2016-2020 Sikka Regency APBD. The method used in this research is mixed method research which combines quantitative and qualitative approaches.